2023
DOI: 10.1038/s41398-023-02356-y
|View full text |Cite|
|
Sign up to set email alerts
|

Therapeutic strategies for autism: targeting three levels of the central dogma of molecular biology

Abstract: The past decade has yielded much success in the identification of risk genes for Autism Spectrum Disorder (ASD), with many studies implicating loss-of-function (LoF) mutations within these genes. Despite this, no significant clinical advances have been made so far in the development of therapeutics for ASD. Given the role of LoF mutations in ASD etiology, many of the therapeutics in development are designed to rescue the haploinsufficient effect of genes at the transcriptional, translational, and protein level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 186 publications
0
8
0
Order By: Relevance
“…The molecular pathomechanism and phenotypic presentation of the KMT2-associated NDDs make them attractive candidates to be considered for ASO strategies. In general, several reports support the notion that the KMT2-associated NDDs would benefit from ASO treatments [86,87].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The molecular pathomechanism and phenotypic presentation of the KMT2-associated NDDs make them attractive candidates to be considered for ASO strategies. In general, several reports support the notion that the KMT2-associated NDDs would benefit from ASO treatments [86,87].…”
Section: Discussionmentioning
confidence: 94%
“…ASO-based treatments are emerging as therapeutic options for an increasing number of rare genetic disorders, including NDDs [16,86,87]. The molecular pathomechanism and phenotypic presentation of the KMT2-associated NDDs make them attractive candidates to be considered for ASO strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autism spectrum disorder (ASD) is a neurodevelopmental disorder affecting almost 1% of children, characterized by impairments in language and social interaction coupled with various degrees of intellectual disability (ID) [ 64 ]. Several studies have demonstrated a strong association between rare de novo and inherited copy number variants (CNV) with ASD.…”
Section: Saha In Neurodevelopmental and Psychiatric Diseases: Current...mentioning
confidence: 99%
“…Vector transport has considerable therapeutic potential, but limitations in its in vivo delivery have been reported, including immunogenicity leading to an immune response, difficulty in controlling the release rate, and high loss rate. [4] The use of cell proliferation to remodel diseased tissue is a promising approach in regenerative medicine, known as cell therapy. [5] The effectiveness of cell therapy is primarily influenced by the type and physicochemical properties of the cells.…”
Section: Introductionmentioning
confidence: 99%